1996
DOI: 10.1128/mcb.16.8.4426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonsense Mutations on Nuclear and Cytoplasmic Adenine Phosphoribosyltransferase RNA

Abstract: We have analyzed Chinese hamster ovary (CHO) cell mutants bearing nonsense codons in four of the five exons of the adenine phosphoribosyltransferase (aprt) gene and have found a pattern of mRNA reduction similar to that seen in systems studied previously: a decrease in steady-state mRNA levels of 5-to 10-fold for mutations in exons 1, 2, and 4 but little effect for mutations in the 3-most exon (exon 5). Nuclear aprt mRNA levels showed a similar decrease. Nonsense-containing aprt mRNA decayed at the same rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 64 publications
4
50
0
Order By: Relevance
“…Moreover, there was no difference in the densities of in-frame and out-of-frame stop codons in either set. We believe our approach, leading to the opposite conclusion, represents a more direct test of the hypothesis in question.These conclusions are in agreement with several genetic studies in which nonsense mutations that did not affect splicing were described, for example, in the genes for dhfr (Urlaub et al 1989), aprt (Kessler andChasin 1996), or hprt (Valentine 1998). Similarly, no nonsense mutations were found among 70 mutants of a three-exon dhfr minigene selected for skipping of the central exon (Chen and Chasin 1993).…”
supporting
confidence: 79%
“…Moreover, there was no difference in the densities of in-frame and out-of-frame stop codons in either set. We believe our approach, leading to the opposite conclusion, represents a more direct test of the hypothesis in question.These conclusions are in agreement with several genetic studies in which nonsense mutations that did not affect splicing were described, for example, in the genes for dhfr (Urlaub et al 1989), aprt (Kessler andChasin 1996), or hprt (Valentine 1998). Similarly, no nonsense mutations were found among 70 mutants of a three-exon dhfr minigene selected for skipping of the central exon (Chen and Chasin 1993).…”
supporting
confidence: 79%
“…Given that bulk translation is cytoplasmic in all eukaryotic systems, an unexpected finding was that mammalian NMD occurs in association with nuclei Kessler and Chasin 1996;Wilkinson and Shyu 2002). In addition, other observations in mammalian systems have shown that a PTC can affect specific nuclear events, such as alternative splicing and 3 end formation (Brogna 1999;Wang et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The first invokes a nuclear scanning model, which requires nuclear translation (Kessler and Chasin 1996). The second suggests that cytoplasmic translation begins during export of RNA from the nucleus to the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Here, we studied the role of UPF1 by examining the changes in abundance and decay rates of transcripts that respond to depletion of UPF1, using a recently developed inhibitor-free genomewide method for measuring RNA stability: 5'-bromo-uridine immunoprecipitation chase-deep sequencing analysis (BRICseq). 48 BRIC-seq involves pulse-labeling endogenous RNAs with 5'-bromo-uridine (BrU) and measuring the ongoing decrease in RNA levels over time by deep sequencing, without the use of transcriptional inhibitors.…”
Section: Identification Of Hundreds Of Novel Upf1 Targetmentioning
confidence: 99%